Effective advocacy in social work - Dalrymple, Jane 1951-; Boylan, Jane (Social work in action., 2013)
Advocacy is an essential skill for social workers who need to be able to speak confidently on behalf of service-users in a range of situations. In this book, Jane Dalrymple and Jane Boylan explore the theory and research behind advocacy and draw on a range of case studies to demonstrate how to achieve best practice.